Violence brief interventions: a rapid review - Donnelly, Peter D. (Aggression and violent behavior, 2014)
Provision of a Violence Brief Intervention (VBI) to young men undergoing treatment for a violent injury may represent a teachable moment for the prevention of future interpersonal violence in Scotland. Prior to intervention design, a rapid review of the research literature was necessary to examine existing programmes. After title and abstract screening, eight distinct VBIs were identified from full texts. Whilst none of the programmes were a perfect match for our intervention goals, they did demonstrate the potential effectiveness of brief interventions for violence prevention at both cognitive and behavioural levels. Key themes of successful interventions included brief motivational interviewing as an effective method of engaging with at-risk participants and encouraging change, the utility of social norms approaches for correcting peer norm misperceptions, the usefulness of working with victims of violence in medical settings (particularly oral and maxillofacial surgeries), the importance of addressing the role of alcohol after violent injury, the advantages of a computer-therapist hybrid model of delivery, and the need for adequate follow-up evaluation as part of a randomised control trial. This information has been used to design a VBI which is currently under evaluation